What do tree-related microhabitats tell us about the abundance of forest-dwelling bats, birds, and insects?. (15th June 2020) - Basile, Marco; Asbeck, Thomas; Jonker, Marlotte; Knuff, Anna K.; Bauhus, Jürgen; Braunisch, Veronika; Mikusiński, Grzegorz; Storch, Ilse
Abstract: Retaining trees during harvesting to conserve biodiversity is becoming increasingly common in forestry. To assess, select and monitor these habitat trees, ecologists and practitioners often use Tree-related Microhabitats (TreMs), which are assumed to represent the abundance and diversity of environmental resources for a wide range of forest-dwelling taxa. However, the relationship between TreMs and forest organisms is not fully understood. In this context, we attempted to identify and quantify the links between TreMs and three groups of forest organisms: insects, bats, and birds. Specifically, we tested whether species abundance is influenced by TreM abundance, either as direct predictor or as mediator of environmental predictors. We collected data in 86 temperate, 1-ha mixed forest plots and employed a hierarchical generalized mixed model to assess the influence of seven environmental predictors (aspect, number and height of standing dead trees, cover of herb and shrub layer, volume of lying deadwood, and terrain ruggedness index (TRI)) on the abundance of TreMs (15 groups) on potential habitat trees, insects (10 orders), bats (5 acoustic groups) and birds (29 species) as a function of seven environmental predictors: aspect, number and height of standing dead trees, cover of herb and shrub layer, volume of lying deadwood, and terrain ruggedness index (TRI). This allowed us to generate a correlation matrix with potential links between abundances of TreMs and co-occurring forest organisms. These correlations and the environmental predictors were tested in a structural equation model (SEM) to disentangle and quantify the effects of the environment from direct effects of TreMs on forest organisms. Four TreM groups showed correlations > |0.30| with forest organisms, in particular with insects and bats. Rot holes and concavities were directly linked with three insect groups and two bat groups. Their effect was smaller than effects of environmental predictors, except for the pairs "rot holes – Sternorrhyncha" and "rot holes – bats" of the Pipistrellus group. In addition, TreMs had indirect effects on forest organisms through mediating the effects of environmental predictors. We found significant associations between two out of fifteen TreM groups and five out of 44 forest organism groups. These results indicate that TreM abundance on potential habitat trees is not suited as a general indicator of the species abundance across broad taxonomic groups but possibly for specific target groups with proven links. Highlights: Tree-related Microhabitats (TreMs) have been proposed as forest biodiversity indicators. The association between TreMs and forest organisms is investigated using multi-species abundance models. The abundance of TreMs is weakly correlated with the abundance of forest organisms. Direct effects of TreM abundance on some forest organisms are found. Positive associations between TreMs and species groups may be used to specify conservation goals.